Kekerasan terhadap Perempuan dalam Ketimpangan Relasi Kuasa: Studi Kasus di Rifka Annisa Women's Crisis Center - Muhammad Rifa'at Adiakarti Farid (Sawwa: Jurnal Studi Gender, 2019)
This study aims to determine the causes of acts of violence and acts of sexual harassment against women. This action can occur by anyone and anywhere that is closely related to health and human rights. Acts of violence are often used as a way to maintain and force the subordination of women against men. This research uses descriptive qualitative method at Rifka Annisa Women’s Crisis Center. Acts of violence and acts of sexual harassment against women occur because of the low mindset of the community about equality of men and women who are intertwined between fellow interactions, both are equally disadvantaged in the situation. The result of this study, there is a single factor causing violence against women, namely because of socio-cultural factors or because of the imbalance of power relations which causes the subordination of women.